Microhábitats de foraminíferos bentónicos en la ría de Vigo y su aplicación a la interpretación paleoecológica. - Vilas, Federico; Diz, P.; Francés, G. (Journal of Iberian Geology, 2000)
In this work living and dead benthic foraminifera assemblages from the central axis of the ria de Vigo have been analysed. The main goals were: establishing the environmental parameters controlling benthic foraminifera microhabitats, determining the taphonomic effects, and stating the elements for an accurate paleoecological interpretation of the rias environment. The living assemblages show that benthic foraminifera distribution in the studied area reflects the dynamic equilibrium with the environmental conditions. The sharp spatial and seasonal changes observed are caused by organic matter supply fluctuations. Nevertheless, summer upwelling events produce an excess of organic flux to the bottom which accelerates the oxygen consumption into the sediment. So the oxygenation level becomes the main limiting parameter for infaunal species. As consequence, benthic foraminifera microhabitats are not stable, but they change according to food and oxygen availability. On the other hand, the dead assemblages show similar features to those from living ones. Then, the dead assemblages are an accurate expression of the paleoenvironmental conditions. However some qualitative and quantitative differences should be taken into account for a better understanding of the fossil record. Several species are more abundant in the dead assemblages than in the living ones, whereas there are some taxa that are more frequent alive. These taxa were destroyed by fossildiagenetic processes and thus are underestimated in the dead assemblages.